Evaluation of the Constant Fraction Time-Over-Threshold (CF-TOT) method for neutron-gamma pulse shape discrimination. (1st May 2022) - Roy, A.; Vartsky, D.; Mor, I.; O. Cohen, E.; Yehuda-Zada, Y.; Beck, A.; Arazi, L.
Abstract: The use of Time-over-Threshold (TOT) for the discrimination between fast neutrons and gamma-rays is advantageous when large number of detection channels are required due to the simplicity of its implementation. However, the results obtained using the standard, Constant Threshold TOT (CT-TOT) are usually inferior to those obtained using other pulse shape discrimination (PSD) methods, such as Charge Comparison or Zero-Crossing approaches, especially for low amplitude neutron/gamma-ray pulses. We evaluate another TOT approach for fast neutron/gamma-ray PSD using Constant-Fraction Time-over-Threshold (CF-TOT) pulse shape analysis. The CT-TOT and CF-TOT methods were compared quantitatively using digitized waveforms from a liquid scintillator coupled to a photomultiplier tube as well as from a stilbene scintillator coupled to a photomultiplier tube and a silicon photomultiplier. The quality of CF-TOT neutron/gamma-ray discrimination was evaluated using Receiver Operator Characteristics curves and the results obtained with this approach were compared to that of the standard CT-TOT method. The CF-TOT PSD method results in > 99.9% rejection of gamma-rays with > 80% neutron acceptance, much better than CT-TOT.